Cosmopolitan Literacies, Social Networks, and "Proper Distance": Striving to Understand in a Global World. Issue 1 (January 2014) - Hull, Glynda A.; Stornaiuolo, Amy; Hansen, David T.
Abstract How are identities as cosmopolitan citizens realized in practice, and how can dialogue be fostered across differences in culture, language, ideology, and geography? More particularly, how might young people be positioned to develop effective and ethical responses, in our digital age, to local and global concerns? Such are the questions we addressed in a design‐based research project that linked young people around the world via a private social network. In effect, we studied cosmopolitanism "on the ground, " as youth on the cusp of adulthood came to think and act reflexively about the opportunities, responsibilities, and challenges of intercultural, cross‐geographic communication in a global, digital world. To analyze the conversations and creative artifacts exchanged by groups of youth in New York City and in India, we invoked the cosmopolitan construct of "proper distance, " asking how participants gauged their relationship to their readers. We identified three stances that composers adopted in their efforts to communicate with and understand their audiences—proximal, reflexive, and reciprocal—and we demonstrated how such stances were manifested semiotically and relationally. This study contributes to a growing literature on the relationship of globalization to education and on cosmopolitanism as one response to this confluence. It demonstrates in empirical, interactional detail the complexity and challenge of learning to communicate, create, and understand across difference, as well as the potential of youth to engage those complexities ethically and to work at comprehending their subtleties. It further illuminates the centrality, for our youthful participants and their cosmopolitan project, of being able to compose in multiple and conjoined modes, and it reanimates the rhetorical construct of "audience" for digital and global times.